1992
DOI: 10.1111/j.1748-1716.1992.tb09402.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates of minke whales (Balaenoptera acutorostrata) in cold water

Abstract: Body temperature, blubber thickness and lung capacity (Vc) were recorded in newly killed minke whales, while respiratory frequency (f) was determined in free-swimming animals. Mean deep (thoracic) body temperature was 34.7 +/- 0.8 (SD) degrees C (n = 14). Weighted mean core/blubber interface temperature in animals caught in 2.5-5.5 degrees C water was 28.8 +/- 1.7 degrees C (n = 8). The minimum average rate of sensible heat loss (HLs) was 3.81 +/- 0.53 (SD) W kgw-0.75 (n = 8) in animals with body masses (w) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 21 publications
1
74
2
Order By: Relevance
“…Diet studies and diving experiments (Blix and Folkow, 1995;Haug et al, 2002) indicate that minke whales primarily feed in the upper 100 m of the water column. Measurements of dive duration have indicated that minke whales usually stay submerged in dives lasting between 4 and 6 min (Folkow and Blix, 1993). Harp seals use the entire water column but are obviously short-duration divers that normally stay submerged for less than 10 min which would leave very little time at depth if the animal chose to dive as deep as 300 m (Nordøy et al, 2008).…”
Section: Discussion Possible Mechanisms In Predation and Competitionmentioning
confidence: 99%
“…Diet studies and diving experiments (Blix and Folkow, 1995;Haug et al, 2002) indicate that minke whales primarily feed in the upper 100 m of the water column. Measurements of dive duration have indicated that minke whales usually stay submerged in dives lasting between 4 and 6 min (Folkow and Blix, 1993). Harp seals use the entire water column but are obviously short-duration divers that normally stay submerged for less than 10 min which would leave very little time at depth if the animal chose to dive as deep as 300 m (Nordøy et al, 2008).…”
Section: Discussion Possible Mechanisms In Predation and Competitionmentioning
confidence: 99%
“…Other studies on common minke whales (B. acutrostrata) in the Northern Hemisphere have shown a tendency for a diurnal feeding activity (Haug et al, 1997;Lindstrøm et al, 1998). In the eastern North Atlantic and western North Pacific, they might not feed at night (Folkow and Blix, 1993;Haug et al, 1997;Tamura, MS 1998). The diurnal pattern seems to be similar to that found in North Atlantic fin whales (Vikingsson 1997).…”
Section: The Diurnal Feeding Rhythmmentioning
confidence: 99%
“…Recent studies in Norway have further developed this work as a part of extensive research into the role of marine mammals in Norwegian waters (e.g. Markussen et al, 1992;Folkow and Blix, 1992;Haug et al, 1996;Nordøy et al, 1995).…”
Section: Introductionmentioning
confidence: 99%